Prospects of essential oil loaded nanosystems for skincare - Neha Kashyap; Amrita Kumari; Neha Raina; Foziyah Zakir; Madhu Gupta (Elsevier, 2022)
Nanotechnology is playing a crucial role in the development of cosmeceuticals for skin care. Essential oils are volatile molecules with complex blends of various derivatives namely terpenoids, aliphatic compounds, phenol derived compounds. They have been widely used for ages due to their various properties such as virucidal, bactericidal, fungicidal, local anaesthetic, anti-inflammatory, analgesic and so on. Essential oils are preferred over the synthetic traditionally used drugs as they are comparatively safer for the skin. Novel nanosystems such as liposomes, niosomes, nanoemulsions, solid lipid nanoparticles, dendrimers and nanospheres, are used for the delivery of essential oils to enhance the penetration through the skin. These nanocarriers provide controlled release and improve the stability of natural components. Moreover, nanotechnology-based skin care products have an aesthetic appeal to them with prolonged effects on the application site. This review outlines the role of various essential oils in skin cosmetics. The different nanotechnology used in essential oil-based formulations and the mechanisms involved in their skin penetration has been highlighted. However, increased skin permeation would also mean toxic effects and can nanotechnology be moulded into non-toxic formulations? The present review discusses these aspects.